Increased Dysfunctional and Plastic Regulatory T Cells in Idiopathic Orbital Inflammation - Chen, Jingqiao; Ye, Huijing; Xiao, Wei; Mao, Yuxiang; Ai, Siming; Chen, Rongxin; Lian, Xiufen; Shi, Lu; Wang, Xing; Bi, Shaowei; Yang, Shenglan; Ji, Xian; et al. (Frontiers in Immunology, 2021)
Background: Idiopathic orbital inflammation (IOI) is a disfiguring and vision-threatening fibroinflammatory disorder. The pathogenesis of IOI has not been elucidated. We sought to clarify the regulatory T cell (Treg) distribution and function in patients with IOI. Methods: The frequency, phenotype and function of Tregs were identified by multicolor flow cytometry and in vitro cell functional assays. Plasma and tissue samples were obtained to investigate cytokines, chemokines and their receptors of interest by relative real-time polymerase chain reaction (PCR) and Luminex assays. Results: Compared with healthy subjects, patients with IOI exhibited obvious increases of Tregs in peripheral blood and affected orbital tissues. Circulating Tregs from patients with IOI were significantly more polarized to a Th17-like phenotype with defective regulatory function, whereas orbit-derived Tregs were polarized to a Th2-like phenotype. Furthermore, ST2 expression levels in circulating Tregs and interleukin (IL)-33 mRNA levels in orbital tissues were decreased in IOI. IL-33 restored the suppressive function of Tregs, reduced interferon (IFN)-γ production by Tregs and decreased the activation of orbital fibroblasts (OFs) cocultured with Tregs in IOI. Conclusion: Increased Tregs with proinflammatory and profibrotic polarization were first identified in IOI, suggesting that Treg plasticity and heterogeneity plays an essential role in IOI pathogenesis. Additionally, our study identified a regulatory effect of IL-33 on inflammation and fibrosis in IOI. Reversing the plastic Tregs via IL-33 might be a potential option for IOI patients.